The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1038/sj.onc.1201047
|View full text |Cite
|
Sign up to set email alerts
|

The 230 kDa mature form of KDR/Flk-1 (VEGF receptor-2) activates the PLC-γ pathway and partially induces mitotic signals in NIH3T3 fibroblasts

Abstract: KDR/Flk-1 tyrosine kinase, one of the two receptors for Vascular Endothelial Growth Factor (VEGF) has been shown to generate the major part of mitotic signals in endothelial cells, although the mechanisms are poorly understood. Here we examined the processing and signal transduction of KDR/Flk-1. Both in endothelial cells and in NIH3T3 cells expressing KDR/Flk-1, an immature form of KDR/Flk-1 with a molecular mass of about 150 kDa was glycosylated to create a 200 kDa intermediate, and after further glycosylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
233
1
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(257 citation statements)
references
References 29 publications
(36 reference statements)
20
233
1
3
Order By: Relevance
“…However, ERK1/2 may not play a major role in this system, since speci®c inhibition of ERK1/2 by PD98059 exhibited only a marginal e ect on vinculin assembly and phosphorylation of FAK and paxillin. Previous reports indicate that VEGF, by binding to KDR, activates ERK1/2 via a phospholipase Cg (PLCg)-PKC-dependent pathway (Seetharam et al, 1995;Guo et al, 1995;Takahashi and Shibuya, 1997). We observed that speci®c inhibition of PKC by GF109203X completely abrogated vinculin assembly as well as DNA sysnthesis.…”
Section: Discussionmentioning
confidence: 49%
“…However, ERK1/2 may not play a major role in this system, since speci®c inhibition of ERK1/2 by PD98059 exhibited only a marginal e ect on vinculin assembly and phosphorylation of FAK and paxillin. Previous reports indicate that VEGF, by binding to KDR, activates ERK1/2 via a phospholipase Cg (PLCg)-PKC-dependent pathway (Seetharam et al, 1995;Guo et al, 1995;Takahashi and Shibuya, 1997). We observed that speci®c inhibition of PKC by GF109203X completely abrogated vinculin assembly as well as DNA sysnthesis.…”
Section: Discussionmentioning
confidence: 49%
“…Nonetheless, various lines of evidence in different tumor types suggest that the VEGF/VEGFR-2 system plays an important role in the regulation of tumor cell growth through the activation of the mitogen-activated protein kinase pathway and, subsequently, the mitogenic response. 56,57 It also is possible that, like endothelial cells, activity of the VEGF/VEGFR-2 system in craniopharyngiomas may be linked to the increasing permeability of epithelial cells and cyst formation. This signaling pathway provides an intriguing mechanism that may establish a direct correlation between VEGF expression and tumor cyst formation, as observed by Vaquero et al 22 in their study of craniopharyngiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the p42/44 MAP kinase pathway by VEGF and subsequent cell proliferation has been documented for many types of endothelial cells (Seetharam et al, 1995;D'Angelo et al, 1995;Rousseau et al, 1997;Kroll and Waltenberger, 1997;Takahashi and Shibuya, 1997;Landgren et al, 1998;Takahashi et al, 1999). Association of VEGFR-2 with Grb2 suggests that activated Ras might be involved in the regulation of the VEGF-induced mitogenic response.…”
Section: Vegfr-2mentioning
confidence: 99%